The Phonological Variation of Pakistani English in comparison to Standard British English: A case study ofBaloch English speaking students in SBKWU, Quetta - Zainab Akram; Dr. Alia Ayub; Hina Arfeen; Mehwish Malghani (Al-Burz, 2017)
With a small amount of language items i.e. words and one variable i.e. phonology, the present atudy aims to exploring the external and internal influences in language change in terms of phonology. The native Balochi speakers while speaking English as a second language face problems in producing some of English language sounds. The phonological differences were observed amongBalochi English speakers in terms of L1 impact on L2 and the influence of social surroundings have been studied in this paper. Employing qualitative mode of inquiry, the present study was conductedin SardarBahadur Khan Women University (SBKWU), Quetta. The population of this paper consisted of Balochi speaking undergraduate studentsfrom three main regions of Baluchistan, from the English Department. Exploiting convenience sampling, three students from each of the three Baloch regional groups and total of 9 students between ages 19 to 22, were selected as subjects of this study. A list of 20 English words based on problematic utterance of phonemes, was recorded while uttered by the students; transcribed and employing the contrastive analysis the results were displayed in a diagrams. First column displays the region, the second depicts the phonemes uttered by the participants and the third shows the Standard British English pronunciation (SBE). This enabled the researcher to trace the phonological variations, influence of L1 on L2 and the geographical influences on the phonological difference.